The Effect of Standing and Different Sitting Positions on Lumbar Lordosis: Radiographic Study of 30 Healthy Volunteers - Cho, Il Youp (Asian Spine J, 2015)
STUDY DESIGN: Radiographic review of healthy volunteers. PURPOSE: To determine the ideal sitting positions by measuring changes in lumbar lordosis (LL) and pelvic parameters (PPs) in various positions. OVERVIEW OF LITERATURE: Prolonged sitting is generally accepted as an important risk factor for low back pain (LBP). It is now recognized that spinopelvic alignment is important for maintaining an energy-efficient posture. METHODS: Lateral spine radiographs of thrirty healthy volunteers (male participants) were taken in standing and five sitting positions. Radiographic measurement of LL and PPs was performed in each position. Statistical analysis was performed to identify a correlation between changes in the LL and PPs in each positions. RESULTS: LL in standing was 48.5°±8.7°. Sitting significantly decreased LL and segmental angle when compared with standing (p<0.05). The lower lumbar segmental angles (L4-5 and L5-S1) significantly decreased in all sitting positions (p<0.05), but the decrease was relatively less on the chair with lumbar support and in the 90°-angled chair. The sacral slope (SS) decreased and the pelvic tilt increased with decreasing LL in the sitting positions. CONCLUSIONS: Sitting causes a reduction in LL and SS when compared with standing. It might cause a spinopelvic imbalance and result in chronic LBP. Our study showed that sitting on a chair with back support induced minimal changes to LL. Consequently, it is proposed that sitting on a chair with back support would be a much more ideal position than sitting on other types of chairs.